2016
DOI: 10.1007/s13219-016-0160-y
|View full text |Cite
|
Sign up to set email alerts
|

Variations in the Thickness of the Cranial Vault in a Deformed Skull from Pre-Hispanic Ancón (Peru)

Abstract: A medical tomodensitometric study (TDM) was performed on a dry skull from the necropolis of Ancón in Peru. The skull, housed at the Muséum national d'histoire naturelle in Paris, displays an anteroposterior, brachycephalic, oblique, asymmetric, and bilobar deformation. TDM permitted 3-D reconstructions of the skull, endocranium, and vault thickness. The external surface displayed deformation and asymmetry in the bone structures and the endocranium demonstrated deformation and asymmetry in the brain lobes and s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 8 publications
0
3
0
Order By: Relevance
“…The DVS results indicate that the asymmetric patterns (type B and C) were common. The SSS communication, either with the right or left TS, might be influenced by the asymmetric development of the occipital lobes due to ACM (Boman et al, 2016; Natahi et al, 2019). The SSS traces were light at the CS, and both the TS and SS were marked.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The DVS results indicate that the asymmetric patterns (type B and C) were common. The SSS communication, either with the right or left TS, might be influenced by the asymmetric development of the occipital lobes due to ACM (Boman et al, 2016; Natahi et al, 2019). The SSS traces were light at the CS, and both the TS and SS were marked.…”
Section: Discussionmentioning
confidence: 99%
“…The ethnohistorical record (Dingwall, 1931) and recent research mention the potential health risk involved in ACM (Lekovic, Baker, Lekovic, & Preul, 2007; Mendonça de Souza, Reinhard, & Lessa, 2008). Side effects, like secondary cranial asymmetry, circulatory problems, necrosis, and infections, could result from the mechanical pressure exerted during the head shaping, the lack of hygiene, blood, and air circulation (Boman, Froment, & Charlier, 2016; Torres‐Rouf, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…More precisely, it has recently been established that external constraints exerted on the skull vault modify the three-dimensional morphology of the orbits and the maxillary sinuses (Khonsari et al 2013a). I has also been shown that the thickness of skull vault bones are modified in the zones where pressure is exerted by the deformation devices (Grupe, 1984;Khonsari et al 2013a;Boman et al 2016).…”
Section: Introductionmentioning
confidence: 99%